MbMYBC1, a M. baccata MYB transcription factor, contribute to cold and drought stress tolerance in transgenic Arabidopsis - Liu, Wanda; Wang, Tianhe; Wang, Yu; Liang, Xiaoqi; Han, Jilong; Han, Deguo (Frontiers in Plant Science, 2023)
The changeable natural environment has an important impact on the growth and development of plants. In order to cope with these inevitable threats in the growth stage, plants have evolved a series of response mechanisms that regulate gene expression. MYB transcription factor (TF) plays a significant role in regulating stress response and stress resistance. In this study, a new MYB TF gene, MbMYBC1, was isolated from the M. baccata and located in nucleus. MbMYBC1 has a positive response to low temperature and drought stress. After being introduced into Arabidopsis thaliana, the physiological indicators of transgenic Arabidopsis had corresponding changes under these two stresses, the activities of catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) increased, the content of proline increased, but the content of chlorophyll and malondialdehyde (MDA) decreased. In addition, its overexpression can also activate the downstream expression of AtDREB1A,AtCOR15aAtERD10B and AtCOR47 related to cold stress and AtSnRK2.4, AtRD29A, AtSOD1and AtP5CS1 related to drought stress. Based on these results, we speculate that MbMYBC1 can respond to cold and hydropenia signals, and can be used in transgenic technology to improve plant tolerance to low temperature and drought stress.